PENERAPAN MODEL PEMBELAJARAN INTERAKTIF SETTING KOOPERATIF (PISK) TERHADAP KEMAMPUAN BERPIKIR KRITIS - Lilis Pebeyanti Simbolon; Haninda Bharata; Caswita Caswita (STKIP Andi Matappa, 2023)
This research was aimed to determine effect of application of the Cooperative Setting Interactive Learning Model (PISK) on the Student’s Mathematical Critical Thinking Ability. The factor that influences students' mathematical critical thinking skills is the lack of use of learning media in schools. This study used One-Group Pretest-Posttest Design, with subject 20 students at SMP Negeri Satu Atap 3 Krui and data were analyzed using descriptive statistics. Based on results of inferential statistical analysis using the t-test formula. Based on results of t-test, tcount 14.75 > ttable 2.093 at 0.05 significance level. This showed that the PISK has an influence on mathematical critical thinking skills on student learning. According to the test criteria H0 was rejected. So, it could be concluded that there is an effect of applying the cooperative setting interactive learning model (PISK) on students' mathematical critical thinking skills.ABSTRACTThis research was aimed to determine effect of application of the Cooperative Setting Interactive Learning Model (PISK) on the Student’s Mathematical Critical Thinking Ability. The factor that influences students' mathematical critical thinking skills is the lack of use of learning media in schools. This study used One-Group Pretest-Posttest Design, with subject 20 students at SMP Negeri Satu Atap 3 Krui and data were analyzed using descriptive statistics. Based on results of inferential statistical analysis using the t-test formula. Based on results of t-test, tcount 14.75 > ttable 2.093 at 0.05 significance level. This showed that the PISK has an influence on mathematical critical thinking skills on student learning. According to the test criteria H0 was rejected. So, it could be concluded that there is an effect of applying the cooperative setting interactive learning model (PISK) on students' mathematical critical thinking skills.Keywords:Critical Thinking, PISK model